2017
DOI: 10.1111/andr.12366
|View full text |Cite
|
Sign up to set email alerts
|

The impact of drugs on male fertility: a review

Abstract: Beside cytotoxic drugs, other drugs can impact men's fertility through various mechanisms. Via the modification of the hypothalamic-pituitary-gonadal axis hormones or by non-hormonal mechanisms, drugs may directly and indirectly induce sexual dysfunction and spermatogenesis impairment and alteration of epididymal maturation. This systematic literature review summarizes existing data about the negative impact and associations of pharmacological treatments on male fertility (excluding cytotoxic drugs), with a vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
143
0
21

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(178 citation statements)
references
References 206 publications
(366 reference statements)
0
143
0
21
Order By: Relevance
“…Male infertility may be related to disorders of spermatogenesis, post-testicular sperm maturation or sexual function ensuring ejaculation of spermatozoa. The impact of drugs on male fertility has recently been reviewed (Semet et al 2017), but still, data on drug effects or side effects on epididymal contractility is sparse. Medications that target smooth musculature potentially interfere with epididymal contraction and thus could prevent the correct maturation and transport of sperm.…”
Section: Potential Side Effects Of Medicationsmentioning
confidence: 99%
“…Male infertility may be related to disorders of spermatogenesis, post-testicular sperm maturation or sexual function ensuring ejaculation of spermatozoa. The impact of drugs on male fertility has recently been reviewed (Semet et al 2017), but still, data on drug effects or side effects on epididymal contractility is sparse. Medications that target smooth musculature potentially interfere with epididymal contraction and thus could prevent the correct maturation and transport of sperm.…”
Section: Potential Side Effects Of Medicationsmentioning
confidence: 99%
“…However, the consequences of APAP and NSAID exposure on the adult reproductive health are still largely unknown (22). A recent study showed the association between APAP and its metabolite p-aminophenol (quantified in urine) and reduced sperm quality in 500 male partners of couples planning for pregnancy (23).…”
mentioning
confidence: 99%
“…Concurrently, there has been a global decline in semen parameters, while the prevalence of hypogonadism remains high (Araujo et al, ; Levine et al, ; Mulligan, Frick, Zuraw, Stemhagen, & McWhirter, ). Though no link has been suggested between NSAID use and these epidemiologic trends, a few small studies over the past decade have suggested a spermatotoxic effect of select NSAIDS (Semet et al, ). Due to a lack of quality evidence, the true effect of NSAIDs on male reproductive physiology has remained understudied and unknown, yet these agents have been generally considered safe for use in men, with little concern for impact on gonadal function.…”
Section: Introductionmentioning
confidence: 99%